Preoperative balance control compensation in patients with a vestibular schwannoma: Does tumor size matter?. Issue 4 (April 2015) - Ribeyre, Laurence; Frère, Julien; Gauchard, Gérome; Lion, Alexis; Perrin, Philippe; Spitz, Elisabeth; Parietti-Winkler, Cécile
Highlights Study about the relationships between balance and tumor size. Unilateral vestibular schwannoma altered postural performances and the tumor size had a bell-like pattern effect on balance control. Implementation of adaptive mechanisms might be determined by the tumor size and the postural compensation does not parallel the vestibular compensation.